Дослідження підходів залучення клієнтів до мережі кав’ярень - Проценко, М. М.; Панфьорова, І. Ю. (ХНУРЕ, 2025)
Nowadays, the world has undergone irreversible changes in understanding what modern, effective business advertising should look like. To a large extent, the changes depend on the rapid development of new technologies, which people have understood how to master wІТh benefІТ for themselves. This work explores methods for attracting a new audience designed for the gastronomic sector. The approaches are described and compared, and their advantages and limІТations are characterized, considering further planning. The most effective of the listed ones is determined.
Keywords: підхід залучення; мережа кав’ярень